Prevalence and factors associated with mental illness among prison inmates: case of Thyolo Prison in Malawi - Nambindo, Joyce Chikwinde (Department of Psychiatry and Mental Health, 2020)
Background: Research predominantly from high income countries suggests that depression and anxiety are highly prevalent among prison inmates. With limited available research from low and middle income countries, this study aimed to estimate the prevalence of possible anxiety and depression among Malawian inmates and identify factors associated with these conditions. Methods: This cross-sectional study was conducted at Thyolo prison situated in the southernmost region in Malawi, from February to March 2018. A total of 378 male prison inmates were interviewed face-to-face using a general questionnaire examining sociodemographic characteristics, prisoners’ previous and current involvement with the prison services, and self-reported mental health problems. Validated screening instruments were used, including the Center for Epidemiologic Studies Depression scale (CES-D) to measure depression; while the Beck Anxiety Inventory (BAI) was used to measure symptoms of anxiety. Multiple logistic regression analyses were conducted to determine the association between anxiety, depression and related variables. Results: The prevalence of possible anxiety disorder and depressive disorder was 62.7% and 72.5% respectively. After adjusting for the effects of the other variables in the model, a multiple logistic regression found that anxiety was significantly associated with no support (AOR 1.65 95% CI: 1.02-2.66) and a previous mental disorder diagnosis prior to imprisonment (AOR 2.07 95% CI: 1.05-4.07); while depression was significantly associated with no support (AOR 5.19 95% CI: 2.66-10.14), and having two or more traumatic events (AOR4.30 95% CI 1.65-11.23). However, being divorced (AOR 0.12, 95% CI: 0.04-0.35) was found to be a protective factor for depression. In addition to this, no support (AOR 2.24 95% CI: 1.36-3.69) and a previous mental disorder diagnosis prior to imprisonment (AOR 2.10 95% CI: 1.05-4.22) were significantly associated with comorbid depression and anxiety. Conclusion: This study provided valuable insights into the prevalence and risk factors associated with possible depression and anxiety among prison inmates in Malawi. Therefore, regular screening of prison inmates for early detection and treatment of mental disorders would be beneficial to improve the quality of life of prison inmates.